Pengaruh Temperatur Temperring Pada Proses Heat Treatment Baja ST 60 Dengan Media Pendingin Oli Terhadap Kekerasan Dan Struktur Mikro - Wajilan, Wajilan; Hariyanto, Agus; Suwarto, Suwarto (Journal of Applied Mechanical Engineering and Renewable Energy, 2024)
Steel that has been hardened is brittle and not suitable for use. Through the tempering process, the hardness and brittleness can be reduced until it meets the requirements for use. Hardness decreases, tensile strength will also decrease while the ductility and toughness of steel will increase. This research aims to determine the effect of tempering temperature in the heat treatment process of ST 60 steel with oil cooling media on hardness distribution and microstructure. The tempering process is carried out at temperatures of 500°C, 400°C, and 300°C with a hardening temperature of 950°C using Mesran SAE 40 Oil Quenching. The method used in this research is experimental research for the specimen is ST 60. The composition test results show that the material The base is included in the medium carbon steel group or medium carbon steel with a carbon content of 0.452%. Hardness testing used a Micro Hardness Tester where the hardness of the tempered specimen was 255.5, and the hardness of the hardened specimen was 189.7 which decreased. Microstructure testing shows that the microstructure of the raw material consists of ferrite and pearlite with balanced crystal shape and size according to the carbon content of 0.452